Transperitoneal rectus sheath block and transversus abdominis plane block for laparoscopic inguinal hernia repair: A novel approach. Issue 3 (20th July 2017) - Nagata, Jun; Watanabe, Jun; Nagata, Masato; Sawatsubashi, Yusuke; Akiyama, Masaki; Tajima, Takehide; Arase, Koichi; Minagawa, Noritaka; Torigoe, Takayuki; Nakayama, Yoshifumi; Horishita, Reiko; Kida, Kentaro; et al.
Abstract: Introduction: A laparoscopic approach for inguinal hernia repair is now considered the gold standard. Laparoscopic surgery is associated with a significant reduction in postoperative pain. Epidural analgesia cannot be used in patients with perioperative anticoagulant therapy because of complications such as epidural hematoma. As such, regional anesthetic techniques, such as ultrasound‐guided rectus sheath block and transversus abdominis plane block, have become increasingly popular. However, even these anesthetic techniques have potential complications, such as rectus sheath hematoma, if vessels are damaged. We report the use of a transperitoneal laparoscopic approach for rectus sheath block and transversus abdominis plane block as a novel anesthetic procedure. Material and Surgical Technique: An 81‐year‐old woman with direct inguinal hernia underwent laparoscopic transabdominal preperitoneal inguinal repair. Epidural anesthesia was not performed because anticoagulant therapy was administered. A Peti‐needle™ was delivered through the port, and levobupivacaine was injected though the peritoneum. Surgery was performed successfully, and the anesthetic technique did not affect completion of the operative procedure. The patient was discharged without any complications. Discussion: This technique was feasible, and the procedure was performed safely. Our novel analgesia technique has potential use as a standard postoperative regimen in various laparoscopic surgeries. Additional prospective studies to compare it with other techniques are required.